Crowdsource Funding via Social Media Platforms - Kevin Byrnes; Aqua Asif; Alex Ng; Sinan Khadhouri; Nikita R. Bhatt; Veeru Kasivisvanathan (Société Internationale d’Urologie Journal)
Crowdfunding involves obtaining financial support for a project through public engagement. It is a form of crowdsourcing, where monetary and non-monetary contributions from the public are obtained for a common aim. Crowdfunding is an increasingly popular way of gaining additional monetary support for medical research projects and may act as a supplement to conventional funding. Social media can influence which projects are likely to be successful. Engagement on social media can increase the funding obtained. In this brief communication, we introduce the concept of crowdfunding, give practical applications, and describe the characteristics of successful campaigns.